Evaluación de estrés en conductores del sitp utilizando la prueba de perfil de estrés de nowack (2018)
This research presents the stress levels in drivers Sitp, establishing the relevant factors associated with stress responses, identifying them by scales such as stress, health habits, prevention, substance abuse, social support network, cognitive strength and well-being psychological, showing each score on these scales and noting which ones are used as protective factors which are a risk for drivers of Stip